1991
DOI: 10.1055/s-2008-1046089
|View full text |Cite
|
Sign up to set email alerts
|

Hämodynamische Befunde bei Patienten mit Retinitis pigmentosa

Abstract: The hemodynamic status of 26 patients with retinitis pigmentosa was examined using video fluorescein angiography. The hemorheological parameters hematocrit, plasma viscosity, erythrocyte aggregation and erythrocyte rigidity were determined. The results were compared to a matched pairs-group. Video angiography showed for retinitis pigmentosa patients a normal arm-retina time and a significant increase of the arteriovenous passage time. The rheological parameters for both groups were within the reference range. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 5 publications
1
23
0
1
Order By: Relevance
“…These results are in agreement with the common clinical finding of retinal vessel attenuation in RP and with previous reports showing retinal blood flow reduction in RP [16,17,18,19,20,21,22,23]. Retinal vessel narrowing is likely due to a substantial loss of photoreceptors [7,24] leading to a decreased oxygen need with consequent reduced blood supply and vasoconstriction [25].…”
Section: Discussionsupporting
confidence: 82%
“…These results are in agreement with the common clinical finding of retinal vessel attenuation in RP and with previous reports showing retinal blood flow reduction in RP [16,17,18,19,20,21,22,23]. Retinal vessel narrowing is likely due to a substantial loss of photoreceptors [7,24] leading to a decreased oxygen need with consequent reduced blood supply and vasoconstriction [25].…”
Section: Discussionsupporting
confidence: 82%
“…30,31 Alterations in the ocular blood flow, as well as in the retinal vessels, have been fully described as being part of the RP pathogenesis. Wolf et al 32 showed that increased arteriovenous transit time and reduced blood flow velocity are early hemodynamic findings of RP patients without any clinically detectable ocular pathology. Furthermore, reduction of the retinal blood vessels, with perivascular pigment deposits, is a funduscopic feature of patients affected by RP.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that neuro-vascular remodelling might also contribute to the pathogenesis of RP [6,7]. In view of the ophthalmoscopically observed reductions in the retinal vessel diameters, and in view of the alterations in the retinal hemodynamics of patients with RP [8,9], we conducted this study to re-assess the retinal blood flow velocity in the patients with RP using a new technology (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%